The Community Conflict Settlement With Customary Law And Local Wisdom Approaches And Law No. 7 Of 2012 Concerning Handling Of Social Conflicts - Adi Gunawan (LEGAL BRIEF, 2022)
In every society, there must be a conflict with different levels and intensities and various causes because social conflict is an inseparable part of the dynamics of people's lives. However, the most important thing about the conflict is how to resolve the conflict and restore peace to society as before. The conflict resolution mechanism that is most often used is customary law and local wisdom because nowadays, Indonesian society is still classified as a traditional society with a magical religio style. If a problem cannot be resolved, it will be resolved using Law No. 7 of 2012 concerning the Handling of social conflicts. This research was library research included in normative sociological research using secondary data equipped with laws and regulations.